The Effect of Career Development and Work Motivation on Job Satisfaction of Employees of the Transportation Department of Central Lampung Regency - Viska Rindra Ningrum; M. Oktaviannur (International Journal of Economics, Business and Innovation Research, 2024)
One component of regional autonomy related to transportation is transportation services. The purpose of this study is to determine how the level of job satisfaction of workers is influenced by professional growth opportunities and intrinsic motivation to work at the Transportation Agency of Central Lampung Regency. A total of 56 people working at the Transportation Agency of Central Lampung Regency were surveyed using this quantitative methodology. A Likert scale questionnaire was used as part of the data collection approach with the help of SPPS version 29. Multiple linear analysis produced the findings. Workers of the Transportation Department of Central Lampung Regency became the research sample. The research findings show that professional growth opportunities and intrinsic motivation in the workplace affect the level of job satisfaction of workers. Workplace satisfaction is influenced by professional growth opportunities and intrinsic motivation, according to the findings of this study.